Efektivitas Pembelajaran Berbasis Proyek dalam Meningkatkan Pemahaman Nilai-Nilai Pancasila pada Siswa SMA Negeri 1 Lalolae - Melin, Melin; Wahida, Sitti Nur; Rahmadani, Natasha; Sopiandy, Dede; Jasrudin, Jasrudin; Putra, Zulfikar (Universitas Hamzanwadi, 2026)
Students' understanding of Pancasila values ​​remains a persistent challenge in Indonesian education. In learning practices, Pancasila values ​​are often delivered textually and memorization-oriented, preventing students from fully internalizing their meaning and implementing them in their daily lives. This situation demands learning innovations that not only emphasize cognitive aspects but also engage students in an effective, contextual, and meaningful way. This study aims to analyze the effectiveness of the Project-Based Learning (PiBL) model combined with comics in improving high school students' understanding of Pancasila values. This study used a weak experimental method with a One Group Pre-test and Post-test design. The subjects were 25 10th-grade students of SMA Negeri 1 Lalolac. Data were collected through essay tests administered before and after the treatment. Data were analyzed using descriptive statistics and N-gain calculations to determine the level of improvement in students' understanding. The results of the study showed an increase in students' average scores from 77.20 in the pre-test to 89.00 in the post-test. The distribution of score categories shifted significantly from a predominance of low and medium scores to a predominance of high scores. The N gain value of 0.56 indicates that the implementation of project-based learning with comics was effective in the medium category. These findings indicate that integrating the PIBL model with comics significantly improved students' understanding of Pancasila values. Therefore, project-based learning with comics can be used as an alternative, innovative learning strategy in Pancasila and Citizenship Education. This model not only improves students' conceptual understanding but also encourages active involvement, creativity, and critical thinking skills in internalizing Pancasila values.